Incentives for merger in a noncompetitive permit market - Cathrine Hagem (Statistics Norway, Research Department, 2008)
A group of small competitive permits traders facing an imperfectly competitive permit market may consider cooperation (merger) to act strategically in the permit market. It is a well-known result in the literature that the horizontal merger of Cournot players may be unprofitable because of the response of nonmerging agents (a negative strategic effect). We show that the strategic effect of a merger among competitive agents substantially differs from the strategic effect of a merger among Cournot players. Furthermore, we show how the profitability of a merger depends on whether the merged agents are on the same side of the market as the preexisting dominant agent(s). These results show how the expected competitive environment in the permit market may determine how potentially large traders such as the US, and group of small, competitive traders, such as the EU countries, organize their permit trade in any follow-up agreement to the Kyoto protocol.
Keywords: D43; Q54; 330; Emission permits; strategic permit trading; mergers; climate agreement; market power.